The effect of yttrium addition on the ratcheting behavior of magnesium - Haoge Shou; Yaoyao Song; Yang Yang; Li Li; Mingjie Wang; Peng Shi; Qi Li; Huanjian Xie; Hongzhou Zhang (PLoS ONE, 2026)
This study provides an in-depth investigation into the influence of yttrium (Y) addition on the ratcheting behavior of magnesium (Mg) alloys under asymmetric cyclic loading. Although pure Mg exhibits higher strength under quasi-static tension, the Mg–Y alloy demonstrates markedly superior resistance to ratcheting during cyclic deformation. The Mg–Y alloy shows a substantially reduced ratcheting strain accumulation rate accompanied by pronounced cyclic hardening, ultimately leading to a significant improvement in fatigue life. Transmission electron microscopy (TEM) reveals that the extensive activation of ⟨c + a⟩ dislocations and the resulting high dislocation density in the Mg–Y alloy play a pivotal role in promoting homogeneous plastic deformation and cyclic hardening, thereby effectively suppressing the accumulation of ratcheting strain. This work provides new insights for the development of high-performance, fatigue resistant Mg alloys.